ROCK1 as a novel prognostic marker in vulvar cancer - Akagi, Erica M.; Lavorato-Rocha, Andre M.; Maia, Beatriz de Melo; Rodrigues, Iara S.; Carvalho, Katia C.; Stiepcich, Monica M.; Baiocchi, Glauco; Sato-Kuwabara, Yukie; Rogatto, Silvia Regina [UNESP]; Soares, Fernando A.; Rocha, Rafael M. (Biomed Central Ltd, 2014)
Background: Vulvar carcinoma is an infrequent tumour, accounting for fewer than 3% of all malignant tumours that affect women, but its incidence is rising in the past few decades. In young women, the manifestation of the vulvar carcinoma is often linked to risk factors such as smoking and HPV infection, but most cases develop in women aged over 50 years through poorly understood genetic mechanisms. Rho-associated coiled-coil-containing protein kinase 1 (ROCK1) has been implicated in many cellular processes, but its function in vulvar cancer has never been examined. In this study, we aimed to determine the prognostic value of ROCK1 gene and protein analysis in vulvar squamous cell carcinoma (VSCC).Methods: ROCK1 expression levels were measured in 16 vulvar tumour samples and adjacent normal tissue by qRT-PCR. Further, 96 VSCC samples were examined by immunohistochemistry (IHC) to confirm the involvement of ROCK1 in the disease. The molecular and pathological results were correlated with the clinical data of the patients. Sixteen fresh VSCC samples were analyzed by array-based comparative genomic hybridization (aCGH).Results: In each pair of samples, ROCK1 levels were higher by qRT-PCR in normal tissue compared with the tumour samples (p = 0.016). By IHC, 100% of invasive front areas of the tumour and 95.8% of central tumour areas were positive for ROCK1. Greater expression of ROCK1 was associated with the absence of lymph node metastasis (p = 0.022) and a lower depth of invasion (p = 0.002). In addition, higher ROCK1 levels correlated with greater recurrence-free survival (p = 0.001). Loss of ROCK1 was independently linked to worse cancer-specific survival (p = 0.0054) by multivariate analysis. This finding was validated by IHC, which demonstrated enhanced protein expression in normal versus tumour tissue (p < 0.001). By aCGH, 42.9% of samples showed a gain in copy number of the ROCK1 gene.Conclusions: ROCK1 is lower expressed in tumour tissue when compared with adjacent normal vulvar epithelia. In an independent sample set of VSCCs, lower expression levels of ROCK1 correlated with worse survival rates and a poor prognosis. These findings provide important information for the clinical management of vulvar cancer.
Keywords: Vulvar carcinoma; ROCK1; qRT-PCR; Immunohistochemistry; aCGH; Prognosis